2013
DOI: 10.1073/pnas.1218062110
|View full text |Cite
|
Sign up to set email alerts
|

Folding and ligand recognition of the TPP riboswitch aptamer at single-molecule resolution

Abstract: Thiamine pyrophosphate (TPP)-sensitive mRNA domains are the most prevalent riboswitches known. Despite intensive investigation, the complex ligand recognition and concomitant folding processes in the TPP riboswitch that culminate in the regulation of gene expression remain elusive. Here, we used single-molecule fluorescence resonance energy transfer imaging to probe the folding landscape of the TPP aptamer domain in the absence and presence of magnesium and TPP. To do so, distinct labeling patterns were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
156
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 115 publications
(170 citation statements)
references
References 49 publications
(89 reference statements)
14
156
0
Order By: Relevance
“…For instance, in most smFRET studies, only a single structural perspective on riboswitch dynamics has been obtained (e.g., from just one FRET pair). The importance of applying multiple structural perspectives in smFRET imaging experiments is exemplified by the present investigation, prior studies of the TPP riboswitch aptamer (49), as well as more complex systems such as DNA helicase (50) and the bacterial ribosome (51,52). Such studies have the potential to uncover unexpected complexities in the structure and dynamics that would be difficult or impossible to discern through bulk techniques.…”
Section: Large Structurally Complex Riboswitches With Pseudoknots Andmentioning
confidence: 81%
“…For instance, in most smFRET studies, only a single structural perspective on riboswitch dynamics has been obtained (e.g., from just one FRET pair). The importance of applying multiple structural perspectives in smFRET imaging experiments is exemplified by the present investigation, prior studies of the TPP riboswitch aptamer (49), as well as more complex systems such as DNA helicase (50) and the bacterial ribosome (51,52). Such studies have the potential to uncover unexpected complexities in the structure and dynamics that would be difficult or impossible to discern through bulk techniques.…”
Section: Large Structurally Complex Riboswitches With Pseudoknots Andmentioning
confidence: 81%
“…S1, Figure 3) that utilizes site-specifically 2-aminopurine (Ap) labeled RNA [35]. For preQ 1 class-I riboswitches, we focused on the specific aptamer sequence from Thermoanaerobacter tengcongensis (Tte) ; for preQ 1 class-II riboswitches, we used the aptamer sequence from Streptococcus pneumoniae (Spn) (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Their results on E. coli thiM TPP aptamer indicated that the P1 switch helix forms a primarily folded structure in the presence of Mg 2+ alone. Also, P1 and other regions around TPP-binding site exhibit an unexpected degree of plasticity which probably results in facilitating the entry and exit of the TPP ligand and influence on gene regulation (Haller et al, 2013).…”
Section: Discussionmentioning
confidence: 99%